Environmental Vulnerability against the Presence of Anopheles spp. with Malaria Cases in North Jakarta - Sinthania Karunia Magdalena Tampubolon; Mursid Raharjo; Sulistiyani Sulistiyani (Jurnal Penelitian Pendidikan IPA, 2023)
There are several locations in DKI Jakarta which have the potential become breeding places for Anopheles spp larvae. The aim of this study was to analyze environmental vulnerability to the presence of Anopheles spp. larvae with malaria cases using a geographic information system approach. This study was an observational study with a cross sectional design. This study was carried out in March – June 2023 in North Jakarta City, DKI Jakarta. The sample consists of data from all malaria patients from 2020-2023 in North Jakarta. The global positioning system coordinates were taken at the addresses of malaria patients. In addition, data on the presence of Anopheles spp. obtained from larval surveys conducted in Cilincing and Penjaringan Sub-Districts and the coordinates for the habitat of Anopheles spp. larvae. The GPS points obtained were then used for spatial analysis. The distribution of malaria cases was random, while the distribution of Anopheles larvae was dispersed. Buffering zone >1000 m from the breeding site indicated that it does not have the potential in malaria transmission due to malaria patients were at a long distance from the breeding site of Anopheles spp. and flight distance of Anopheles spp. not exceeding 1000 m